MEAN PLATELET VOLUME, RED CELL DISTRIBUTION WIDTH, AND LYMPHOCYTE RATIOS AS SURROGATE PREDICTORS OF SUBCLINICAL INFLAMMATION IN SCHIZOPHRENIA: A CROSS-SECTIONAL STUDY - Ahmed Embaby (Euromediterranean Biomedical Journal, 2022)
Inflammation is a key player in schizophrenia pathogenesis. Higher inflammatory indicators like erythrocyte distribution width (RDW), Mean Platelet Volume (MPV), Neutrophil-to-lymphocyte Ratio (NLR), monocyte lymphocyte Ratio (MLR) and Platelet-to-lymphocyte Ratio (PLR) were found in schizophrenic patients compared to healthy controls. This comparative cross-sectional study aimed to find the predictors of subclinical inflammatory process in schizophrenic compared to healthy controls. A consecutive sample of 90 individuals were prospectively enrolled in the study: 45 schizophrenic patients and 45 age- and sex-matched controls. The DSM-5 was used to diagnose schizophrenia. Socio-demographic data and blood samples were collected for both groups. The WBCs, absolute neutrophil count, absolute lymphocytic count, RDW%, MPV were significantly higher; Unlike hemoglobin, significantly lower in schizophrenic group (P<0.05). However, no significant differences between both groups regarding absolute monocyte and platelet Count. NLR was significantly higher while PLR and MLR were significantly lower in schizophrenic group (p<0.05). The MPV, RDW, PLR and NLR were independent predictors of subclinical inflammation in schizophrenic schizophrenia. Marked alteration of RDW, MPV, NLR and PLR reflecting the ongoing inflammatory process in schizophrenic patients and these changes during the course of the disease could be monitored to stand on the disease improvement.